2021
DOI: 10.3390/ma14092309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on Tensile Characteristics of Plain C–Mn Steel with Ultrafine Grained Ferrite/Cementite Microstructure and Coarse Grained Ferrite/Pearlite Microstructure

Abstract: This work investigated the tensile characteristics of plain C–Mn steel with an ultrafine grained ferrite/cementite (UGF/C) microstructure and coarse-grained ferrite/pearlite (CGF/P) microstructure. The tensile tests were performed at temperatures between 77 K and 323 K. The lower yield and the ultimate tensile strengths were significantly increased when the microstructure was changed from the CGF/P to the UGF/C microstructures, but the total elongation and the uniform elongation decreased. A microstructural ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…There was much necking, which meant a high ductility. 15 This was consistent with the nominal engineering stress-strain curve. The SEM tensile fracture morphologies at room temperature exhibited typical dimple fracture, illustrating clear ductile dimples characteristics of microvoid coalescence as shown in Figure 4(b).…”
Section: Resultssupporting
confidence: 82%
“…There was much necking, which meant a high ductility. 15 This was consistent with the nominal engineering stress-strain curve. The SEM tensile fracture morphologies at room temperature exhibited typical dimple fracture, illustrating clear ductile dimples characteristics of microvoid coalescence as shown in Figure 4(b).…”
Section: Resultssupporting
confidence: 82%
“…The higher-magnification SEM micrograph embedded in Figure 2b revealed that the banded structure presented a lamellar arrangement with alternate thin ferrite and cementite layers, i.e., a typical pearlite characteristic. [17] When the cooling rate was ≈5 °C s À1 , the obtained microstructure was consisted of irregular various-sized polygonal-like ferrite grains plus faintly banded structure. In OM micrograph as shown in Figure 2c, the ferrite matrix region was white, and faintly banded structure region was slightly dark.…”
Section: Resultsmentioning
confidence: 95%
“…The grain boundaries hindered dislocation movement. The smaller grain size had the larger proportion of grain boundaries, resulting in a more obvious hindrance [ 14 ]. In addition, the undistorted grain obtained by recrystallization annealing could also reduce the hardness.…”
Section: Resultsmentioning
confidence: 99%